ChemInform Abstract: Expanding Dynamic Kinetic Protocols: Transaminase‐Catalyzed Synthesis of α‐Substituted β‐Amino Ester Derivatives. Issue 14 (8th April 2014) - Cuetos, Anibal; Lavandera, Ivan; Goto, Vicente
Abstract Several enantiopure α‐alkylated β‐amino esters (II)/(III) are obtained via dynamic kinetic resolution employing a kit of transaminases as biocatalysts and isopropylamine as amino donor.